Innovative Technique to Record Neutral Zone for Complete Dentures Using Light Cure Tray Material - Dighe, Triveni; Madhav, V.N.V; Joshi, Snehal; Lambat, Apurva; Kamble, Atharva; Patel, Khushbu (Journal of Neonatal Surgery, 2025)
In resorbed or atrophic ridges, it is very challenging to achieve denture retention because of the loss of bone support. The denture must have some stability in the oral cavity, so the neutral zone technique was developed. Here the inward forces from the cheeks and lips are neutralized by the outward forces from tongue. This creates a zone or area where these forces are balanced, which was known as neutral zone